PENGARUH PENYALURAN DANA ZAKAT PRODUKTIF DAN PEMBINAAN SUMBER DAYA INSANI TERHADAP KESEJAHTERAAN MUSTAHIK UMKM PADA MASA PANDEMI COVID-19 DI LAZISMU KOTA MEDAN - Yuspita Sari; Muhammad Yafiz; Rahmat Daim Harahap (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study aims to find out how the Effect of Productive Zakat Fund Distribution and Human Resource Development on the Welfare of MSME Mustahik During the Covid-19 Pandemic. The research methodology used is Quantitative Research. Data collection techniques using questionnaires, the population in this study amounted to 78 people, the data obtained from the number of mustahik who received productive zakat funds at LAZISMU Medan City, the sample in this study amounted to 78 beneficiaries, using saturated sampling, this study used analytical techniques multiple linear regression. The results showed that the Variable Distribution of Productive Zakat Funds had a strong effect on Mustahik's Welfare. This can be seen from the t arithmetic value of 4.454 > t table of 1.992 with a significance value of 0.001 < 0.05. So that it proves that H1 is accepted. The Human Resource Development Variable has an effect on Mustahik's Welfare. This can be seen from the t-count value of 3.578> t-table of 1.992 with a significance value of 0.005 <0.05. So that it proves that H2 is accepted. Variables of Distribution of Productive Zakat Funds and Human Resources Development have a simultaneous effect on Mustahik's Welfare. This can be seen from the calculated F value of 6.686> F table of 3.12 with a significance value of 0.002 <0.05. Thus proving that H3 is accepted. The coefficient of determination test shows that the distribution of productive zakat funds and human resource development (independent variable) has an effect on Mustahik's Welfare (dependent variable) of 65.1%.